Sobre a ecomorfologia de girinos: as implicações funcionais da variação nas estruturas orais - Annibale, Fabiane Santana (2019)
The role of morphology on animals’ ecology helps us understand the adaptive significance of variation in anatomical structures among species. However, for tadpoles the implications of variation in species morphology on resource use and partitioning among species are poorly understood. This thesis was elaborated in order to better understand tadpoles’ ecomorphology, and is divided into three chapters. The first chapter consists on a bibliographical review and a scientometric analysis on tadpoles’ ecomorphology. Through the data survey we described the tadpoles’ ecomorphological trajectory, quantified the scientific knowledge produced in this study area, and identified the main gaps that may guide future studies. We verified that ecomorphological studies on tadpoles have been increasing over time, with modifications in methodologies and new perspectives to understand the ecology and evolution of tadpoles. However, many of these studies are descriptive or investigate the phenotypic plasticity of larvae in response to predators. Thus, there are still many environmental factors to be explored, as well as the necessity of studying beyond inferences. As such, tadpoles’ ecomorphology will be able to help us understand the diversity of anuran larvae (i.e., ecology and evolution) and with conservation of these animals. Aiming to fill some of these gaps in knowledge, the second and third chapters correspond to researches on how variation in external oral morphology influences tadpoles’ ability to feed on substrates with different properties. In the second chapter we tested the performance of tadpoles feeding on substrates at different orientations. We found that species with similar oral morphology also have similar performances when feeding on substrates positioned at different orientations. Only species that occur at different depths in the environment varied in performance at a specific orientation (i.e. vertical). Among tadpoles that occur in the same place, but vary in terms of external oral morphology, whereas some species have high performances feeding on substrates regardless their orientation, other species are more efficient feeding at specific orientations of substrates. We concluded that these differences in performance may determine how tadpoles select and/or share resources in the environment. In the third chapter, we studied with more details the influence of variation in external oral morphology, testing the species performance when feeding on substrates with different textures. Differences in the number of labial tooth rows and in the marginal papillae configuration affected tadpoles’ grazing performance on substrates with different textures, indicating specializations of feeding behavior. In addition, we verified that tadpoles with the most common oral morphology among anuran larvae had the best performances in comparison to all the other species. This result may help explain the adaptive significance of morphological variation among anuran larvae.